Improvement of Seawater Salt Quality by Hydroextraction Method - Ketut Sumada; Retno Dewati; Suprihatin (Future Science)
Indonesia is one of the salt producing countries that use sea water as a source of raw materials, the quality of salt produced is influenced by the quality of sea water. The resulting average salt quality contains 85-90% NaCl. Those salt quality are still below of the Indonesian National Standard (SNI) for human salt’s consumption sodium chloride content is 94.7 % (dry base) and for industrial salt 98,5 %. The improvement of seawater salt quality can be done by several methods: leaching (hydro-extraction), re-crystallization without chemicals or with chemicals, and ion exchangers. In this study we studied the improvement the quality of seawater salt by hydro-extraction method. The objective of this research to improve the quality of seawater salt by hydro-extraction method. The hydro-extraction is a method to improve the quality of salt by washing with saturated salt solution, this method influence by size of salt (diameter), time of hydro-extraction, saturated salt solution concentration and recycle time of saturated salt solution. Based on the results of the research, the hydro-extraction method can produce salt with purity 99,34 % NaCl. The condition is achieved at 30/40 mesh salt size and the time of use of saturated salt solution 5 times.